Effect of adiposity on differences in carotid plaque burden in studies conducted in Norway and Russia: a cross-sectional analysis of two populations at very different risk of cardiovascular mortality. Issue 5 (6th May 2020) - Imahori, Yume; Frost, Chris; Mathiesen, Ellisiv B; Ryabikov, Andrey; Kudryavtsev, Alexander V; Malyutina, Sofia; Kornev, Michael; Hughes, Alun D; Hopstock, Laila A; Leon, David A
Abstract : Objectives: Large differences exist in the burden of cardiovascular disease (CVD) between Russia and Western European countries including Norway. Obesity prevalence may contribute to the differences. We investigated whether difference in the level of adiposity, assessed using body mass index and waist-to-hip ratio(WHR), could explain intercountry differences in the burden of carotid plaque, a measure of atherosclerosis, in the populations. Design: Cross-sectional analysis. Logistic and linear regression models were used. Setting: We used population-based cross-sectional Know Your Heart (KYH) study in Russia and the Tromsø 7 study (Tromsø 7) in Norway. Participants: 3262 and 1800 men and women aged 40–69 years in KYH and Tromsø 7, respectively. Primary and secondary outcome: The presence of carotid plaques and plaque score assessed using ultrasound. Results: The presence of carotid plaques and plaque score were higher in KYH than Tromsø 7 regardless of age group and sex. A positive association between carotid plaque burden and adiposity was found (OR of having at least one plaque per SD in WHR 1.18 (95% CI 1.06 to 1.31) for men; 1.15 (1.06 to 1.25) for women)) adjusted for age, smoking and education in a pooled analysis of the two studies. There was little evidence of the interaction between study and adiposity. These effects did not differ between the two studies. However, neither adiposity nor CVD risk factors (smoking, systolic blood pressure, cholesterol, glycosylated haemoglobin) explained the higher carotid plaque burden in KYH compared with Tromsø 7. Conclusion: Adiposity, especially abdominal adiposity, is a risk factor for carotid plaque in Russia and Norway, although neither adiposity nor established CVD risk factors explained the higher plaque burden in Russia. To reduce the CVD burden in Russia, beyond prevention and treatment of adiposity, further research is required to understand why Russia has a high burden of atherosclerosis.